The role of Facebook in a survivor's post-assault life: rape on campuses, women activists, and mental health - Witi, Sinethemba Juliet (Rhodes University, Faculty of Humanities, School of Journalism and Media Studies)
The rise of Social Networking Sites (SNSs) has raised concerns about the negative impact social media platforms, and in particular Facebook, has on their users. Research has linked the excessive use of Facebook with mental health challenges such as loneliness, depression, and stress. This research examined how Yolanda Dyantyi, a gender rights activist registered as a student from 2015 to 2017 at Rhodes University, used Facebook as an outlet following the #RUreferencelist protests and her subsequent permanent exclusion from the institution for her role in the protests. The study explored Dyanti's use of Facebook, examining in particular her ongoing activism, her mental health challenges, and her struggles to re-establish herself in a community after the exclusion from Rhodes. The study employed an intersectional feminist theoretical framework and drew on a qualitative content analysis, a semi-structured interview, and the scroll back method to review the Facebook posts she had made. A thematic analysis of the data showed that Dyantyi is a multifaceted, and evolving Facebook user and contrary to existing research her prolific use of Facebook has had positive effects on her mental health and has enabled her to build social capital. The study suggests that activism is an important component to research alongside studies of mental health on such media platforms.
Keywords: Online social networks; Rape in universities and colleges -- South Africa -- Makhanda; Student movements -- South Africa -- Makhanda; College students Mental health -- South Africa -- Makhanda; Sex crimes -- South Africa -- Makhanda; Social media and college students -- South Africa -- Makhanda; Intersectionality (Sociology); Womanism